Pengaruh Model Pembelajaran Group Investigation Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VIII Di SMP Negeri 3 Lintongnihuta Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Eser Haposan Dongoran; Ronny Simatupang; Adiani Hulu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to find out whether there is a positive and significant influence of the Group Investigation learning model on the learning motivation for Christian Religious Education and Character Education of class VIII students at SMP Negeri 3 Lintongnihuta Humbang Hasundutan Regency for the 2023/2024 Academic Year. The method used in this research is quantitative. The population is all 191 students of class VIII of SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year who are Christians and the research sample was determined to be 48 people, namely 25% of the total population. Data was collected using a closed questionnaire with 38 items, of which 20 questionnaire items were for variable X and 18 questionnaire items for variable Y which were compiled by the author based on variable indicators according to expert theory. The results of data analysis show that there is a positive and significant influence of the Group Investigation learning model on the learning motivation of Christian Religious Education and Character Education for class VIII students at SMP Negeri 3 Lintongnihuta, Humbang Hasundutan Regency, Academic Year 2023/2024: 1) Test the analysis requirements: a) test the relationship The positive value obtained is rxy = 0.537 > rtable(=0.05,n=48) = 0.284, thus it is known that there is a positive relationship between variable (=0.05,dk=n-2=46)= 2.021, thus there is a significant relationship between variable ,